1994
DOI: 10.1037/h0079552
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of familial and school-based risk factors for Hispanic Head Start children.

Abstract: The relation of familial and school-based risk factors to socioemotional and learning problems was studied in a sample of Hispanic children in Head Start programs. Socioemotional problems were found to relate most strongly to school-based solitary play, negative peer interaction, and maternal reports of child temperament, while associated learning problems related most strongly to school-based attention span. Significant gender interaction was also identified. Results support use of a culturally sensitive ecol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
(72 reference statements)
0
4
0
Order By: Relevance
“…Grossman and Shigaki (1994) found that cultural factors may distort teacher perceptions of temperament. For example, Hispanic preschool girls may appear to teachers as shy, timid, and withdrawn.…”
Section: Role Of Temperament In Social Competencementioning
confidence: 99%
See 1 more Smart Citation
“…Grossman and Shigaki (1994) found that cultural factors may distort teacher perceptions of temperament. For example, Hispanic preschool girls may appear to teachers as shy, timid, and withdrawn.…”
Section: Role Of Temperament In Social Competencementioning
confidence: 99%
“…However, temperament in young children is influenced by a number of factors such as poor parenting, economic hardships (Sanson, Oberklaid, Pedlow, & Prior, 1991), and cultural norms and beliefs (Chen, Rubin, & Li, 1995;Smart & Sanson, 2001). Grossman and Shigaki (1994) found that cultural factors may distort teacher perceptions of temperament. For example, Hispanic preschool girls may appear to teachers as shy, timid, and withdrawn.…”
Section: Role Of Temperament In Social Competencementioning
confidence: 99%
“…This symptom constellation identified in the study predicts juvenile delinquency and adult criminality (Loeber 1991). The targeted schools were at high risk for mental health problems and delinquency because of a high ratio of economically disadvantaged families (John, Offord, Boyle & Racine, 1995) and high immigrant, ethnic populations (Grossman & Sdigaki, 1994). A letter explaining the goals and methods of the project was sent home to children and their parents.…”
Section: Methodsmentioning
confidence: 99%
“…The marginalization of African America Head Start fathers is in direct contrast to the disproportionate research on the roles of African America Head Start mothers in the lives of their children (Pellegrini et al, 1990;Andrews et al, 1975;Gordon and Guinegh, 1975;Kogan & Gordon, 1975;Grossman ... Shigaki, 1994). Acknowledging the importance of paternal influences on preschoolers, the "Final Report of the Advisory Committee in Head Start Quality and Expansion" (U.S. Dept.…”
Section: Comments Solicited Frommentioning
confidence: 96%